ln(2x)=ln(3y)

Simple and best practice solution for ln(2x)=ln(3y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(2x)=ln(3y) equation:


Simplifying
ln(2x) = ln(3y)

Remove parenthesis around (2x)
ln * 2x = ln(3y)

Reorder the terms for easier multiplication:
2ln * x = ln(3y)

Multiply ln * x
2lnx = ln(3y)

Remove parenthesis around (3y)
2lnx = ln * 3y

Reorder the terms for easier multiplication:
2lnx = 3ln * y

Multiply ln * y
2lnx = 3lny

Solving
2lnx = 3lny

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-3lny' to each side of the equation.
2lnx + -3lny = 3lny + -3lny

Combine like terms: 3lny + -3lny = 0
2lnx + -3lny = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(2x + -3y) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(2x + -3y)' equal to zero and attempt to solve: Simplifying 2x + -3y = 0 Solving 2x + -3y = 0 Move all terms containing l to the left, all other terms to the right. Add '-2x' to each side of the equation. 2x + -2x + -3y = 0 + -2x Combine like terms: 2x + -2x = 0 0 + -3y = 0 + -2x -3y = 0 + -2x Remove the zero: -3y = -2x Add '3y' to each side of the equation. -3y + 3y = -2x + 3y Combine like terms: -3y + 3y = 0 0 = -2x + 3y Simplifying 0 = -2x + 3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 25r-5=55r | | L+23=-1 | | 5(p-2)+2(-3+3p)=-16 | | 170=-t^2+17t+140 | | 40x+4=10x+4 | | y-5=3.14(x-8) | | 20x+5(x+1)=25(x+1)-20 | | 2y+y=20 | | 8+45x-18x=0 | | X^2-6x-2y+11=0 | | 10x-5xy+y=0 | | -2(1+5x)+8(2+8x)=14 | | 75+4x-25=360 | | 7x-6+x=90 | | 15+14y=19 | | x^2-18x-81= | | y=-0.2x+4 | | 6(-3a+6)-5(6a-4)=-40 | | x+12=51 | | 21x+12=7x+12 | | x(x)=435 | | m=4(10)+2(5) | | x(2x-2)=35 | | 2n+10=-3n-5 | | 8x-2(10x-2)=20 | | 75+40x=y | | 23.75=18.75+2B | | X+3=-25 | | 5x+10=10x+10 | | -9n-8=10n-7 | | 2y-17y=72 | | 128=6(7+5x)-4 |

Equations solver categories